Social Studies Concepts: An Analysis of the NAEP and States' Standards. Issue 3 (2nd July 2016) - Lord, Kathleen M.; Noel, Andrea M.; Slevin, Bridgette
ABSTRACT: This study examined the 4th-grade National Assessment of Educational Progress (NAEP) assessments (history, geography, and civics) and 3rd- and 4th-grade social studies standards from nine randomly selected states and organized the content around three global concepts (conflict, movement, discovery) and six specific concepts (war, rebellion, immigration, migration, exploration, invention). The extent to which additional related concepts appeared in both documents was recorded, and alignment between the NAEP and standards was determined. Findings revealed that 3rd- and 4th-graders are learning social studies content that represent these global and specific concepts. However, there is variability among states' standard documents and inconsistencies between what is assessed on the NAEP and what is presented in the standards. In addition, much instruction for these concepts takes place during 4th grade, the same year the NAEP is administered. Implications of these findings, including the urgent need for conceptually based social studies instruction to meet students' knowledge and achievement gaps, are discussed.